Timed-Handwriting Technique (THT) to Increase Students’ Writing Performance - Muh Syafei, Januarius Mujiyanto, Issy Yuliasri; Hendi Pratama (International Journal of Advanced Science and Technology, 2020)
This study aims to investigate the effectiveness and perceptions of students about the Timed-Handwriting Technique (THT) in improving writing performance in the Department of English Education at Muria Kudus University. The method used in this research is a sequential explanatory mixture with an ex post facto experimental design because the independent variables have naturally occurred during writing class. THT compositions and reflections are observed from 21 purposively selected participants. The findings show that THT is effective quantitatively and qualitatively. Quantitatively, THT can improve student writing performance. Qualitatively, THT can improve students’ positive perceptions. The quantitative result is by that of the qualitative one.